(untitled) (Journal of Parents and Teachers, 2026)
In interpersonal dynamics, and particularly in schools, there is what might be termed peer pressure. This article examines the ‘characters’ that emerge in a classroom and the ways in which they react when they fail to fit into the group. A role-play activity is proposed, in which the various characters, each with their own characteristics, are assigned to pupils so that each can internalise and portray their role. Sometimes pupils identify with certain characters freely, but at other times they may be assigned roles by others almost as a caricature, and this is where peer pressure comes into play.